Charge transport in conjugated polymer-semiconductor nanoparticle composite near the percolation threshold - Cardoso, L. S.; Goncalves, G. E.; Kanda, D. H. F. [UNESP]; Bianchi, R. F.; Nagashima, H. N. [UNESP] (Springer, 2017)
This paper describes a new statistical model to predict the frequency dependence of the conductivity of conjugated polymer-semiconductor nanoparticle composites. The model considers AC conduction in an inhomogeneous medium represented by a two-dimensional model of resistor network. The conductivity between two neighboring sites in the polymer matrix and the semiconductor particles is assumed to obey the random free energy barrier model and the Drude model, respectively. The real and imaginary parts of the AC conductivity were determined using the transfer-matrix technique, and the statistical model was applied to experimental data of thin films composed of polyaniline (PANI) and indium-tin-oxide (ITO) nanoparticles. The conductivity critical exponent (s) obtained in two dimensions for PANI/ITO films below the percolation threshold was found to be 2.7, which is greater than the universal value of s described by the classical percolation theory (s = 1.3). This non-universality is explained by the existence of a local electric field distribution in the bulk of the nanocomposite. Finally, these results are discussed in terms of the distribution of potential barriers that vary according to the concentration of ITO amount in the composite.